2009
DOI: 10.1007/s11085-009-9168-8
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Oxidation of Fe3Al and Fe3Al–Zr Intermetallics

Abstract: The oxidation behavior of Fe 3 Al and Fe 3 Al-Zr intermetallic compounds was tested in synthetic air in the temperature range 900-1200°C. The addition of Zr showed a significant effect on the high-temperature oxidation behavior. The total weight gain after 100 h oxidation of Fe 3 Al at 1200°C was around three times more than that for Fe 3 Al-Zr materials. Zr-containing intermetallics exhibited abnormal kinetics between 900 and 1100°C, due to the presence and transformation of transient alumina into stable a-Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 70 publications
3
15
0
Order By: Relevance
“…In order to obtain the required H 2 O fraction (5%), the O 2 gas was passed through boiling distilled water and then through a vertical tube cooled at a well-determined temperature (15°C). The H 2 O fraction was checked using a hygrometer (16). For isothermal ageing tests, the samples were placed in a horizontal furnace for 100h.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain the required H 2 O fraction (5%), the O 2 gas was passed through boiling distilled water and then through a vertical tube cooled at a well-determined temperature (15°C). The H 2 O fraction was checked using a hygrometer (16). For isothermal ageing tests, the samples were placed in a horizontal furnace for 100h.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal contraction associated with cooling causes exfoliation. Other authors confirm very good oxidation resistance of Fe-Al compounds [14,15,16], especially those alloyed with Zr [17,18,19], Nb [20], Ce [21], and Y 2 O 3 [22]. …”
Section: Introductionmentioning
confidence: 92%
“…Experimentally, the formation temperature of a-Al 2 O 3 can be lowered down by doping alloying elements. It is found that the transformation temperature of a-Al 2 O 3 from g-Al 2 O 3 decreased from 950 C to 900 C after the addition of 0.05 at.% Zr in Fe 3 Al [103]; the transformation temperature could be further decreased to 750 C when co-doped by Zr, Nb, C and B elements [93]. It is obvious that the alloying effect in aluminide coatings composed of a FeAl transition layer and an Al 2 O 3 film is closely dependent on the temperature.…”
Section: Temperaturementioning
confidence: 99%